Пошаговое объяснение:
1)12(b²-c²) 4)3m(n²-16)
2)2c(a²-b²) 5)7y(y-1)
3)5(a²-4) 6)a³(1-a²)
1) 12b² – 12c² = 12(b²–c²) = 12(b–c)(b+c);
2) 2a²c – 2b²c = 2c(a²–b²) = 2c(a–b)(a+b);
3) 5a² – 20 = 5(a²–4) = 5(a²–2²) = 5(a–2)(a+2);
4) 3mn² – 48m = 3m(n²–16) = 3m(n²–4²) = 3m(n–4)(n+4);
5) 7y³ – 7y = 7y(y²–1) = 7y(y–1)(+1);
6) a³ – a^5 = a³(1–a²) = a³(1–a)(1+a)
Пошаговое объяснение:
1)12(b²-c²) 4)3m(n²-16)
2)2c(a²-b²) 5)7y(y-1)
3)5(a²-4) 6)a³(1-a²)
1) 12b² – 12c² = 12(b²–c²) = 12(b–c)(b+c);
2) 2a²c – 2b²c = 2c(a²–b²) = 2c(a–b)(a+b);
3) 5a² – 20 = 5(a²–4) = 5(a²–2²) = 5(a–2)(a+2);
4) 3mn² – 48m = 3m(n²–16) = 3m(n²–4²) = 3m(n–4)(n+4);
5) 7y³ – 7y = 7y(y²–1) = 7y(y–1)(+1);
6) a³ – a^5 = a³(1–a²) = a³(1–a)(1+a)